2008
DOI: 10.1371/journal.pone.0002721
|View full text |Cite
|
Sign up to set email alerts
|

TAF6δ Controls Apoptosis and Gene Expression in the Absence of p53

Abstract: BackgroundLife and death decisions of metazoan cells hinge on the balance between the expression of pro- versus anti-apoptotic gene products. The general RNA polymerase II transcription factor, TFIID, plays a central role in the regulation of gene expression through its core promoter recognition and co-activator functions. The core TFIID subunit TAF6 acts in vitro as an essential co-activator of transcription for the p53 tumor suppressor protein. We previously identified a splice variant of TAF6, termed TAF6δ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(57 citation statements)
references
References 65 publications
5
49
1
Order By: Relevance
“…Our previous work demonstrated that TAF6δ induces apoptosis independently of p53 [5]. Interestingly, the current transcriptome data show that TAF6δ induces the expression of several p53 target genes (Figure 2A and Additional File 3).…”
Section: Resultsmentioning
confidence: 67%
“…Our previous work demonstrated that TAF6δ induces apoptosis independently of p53 [5]. Interestingly, the current transcriptome data show that TAF6δ induces the expression of several p53 target genes (Figure 2A and Additional File 3).…”
Section: Resultsmentioning
confidence: 67%
“…Particularly illustrative of the regulatory power of alternative TAFs is that overexpression of TAF6, or induction of endogenous TAF6 expression, in HeLa cells induces apoptotic cell death and the transcription of pro-apoptotic genes in the absence of an apoptotic signal. Surprisingly, the pro-apoptotic transcription factor p53 (TP53) is not required for TAF6-dependent transcription or apoptosis (Wilhelm et al, 2008). Similarly, overexpression of TAF4b in non-granulosa cells, such as mouse NIH/3T3 fibroblasts, results in the expression of genes that are TAF4b dependent in ovaries and granulosa cells and that are not normally expressed in non-granulosa cells (Geles et al, 2006).…”
Section: Master Transcriptional Control By Tafsmentioning
confidence: 99%
“…3A), and because modified antisense RNA oligonucleotides that anneal to it can shift the splicing from the major to the pro-apoptotic δ form in living cells [3]. The ESEfinder algorithm [34] was employed and detected a potential SF2 binding site in exon 2a (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together these findings suggest that the major anti-apoptotic TAF6α splice variant possesses oncogenic potential. In stark contrast, the minor TAF6δ splice variant has pro-apoptotic activity evoking a potential tumor suppressor activity [1], [2], [3]. It is conceivable that anti-apoptotic TAF6α expression can be decoupled from pro-apoptotic TAF6δ in certain tumor types.…”
Section: Discussionmentioning
confidence: 99%